Investigation of the combustion of exhaust gas recirculation in diesel engines with a particulate filter and selective catalytic reactor technologies for environmental gas reduction - Megavath Vijay Kumar; Alur Veeresh Babu; Ch. Rami Reddy; A. Pandian; Mohit Bajaj; Hossam M. Zawbaa; Salah Kamel (Case Studies in Thermal Engineering, 2022)
The use of diesel engines has increased dramatically in recent years, as has the number of exhaust emissions. These emissions have the potential to endanger Mother Nature and the living species within it. Governments all over the world have introduced legislative rules on exhaust emission reduction in order to limit the number of emissions released into the environment through the use of global sustainable development technologies. This has compelled automobile manufacturers to create a variety of diesel emission reduction systems, the most important of which are the Diesel Particulate Filter (DPF), Exhaust Gas Recirculation (EGR), and Selective Catalytic Reactor (SCR). The primary goal of this research work is to reduce diesel engine exhaust gas emissions by utilizing emission reduction systems such as DPF, EGR, and SCR. Here, various combinations of the aforementioned emission reduction systems were tested to determine the best possible combination that had the greatest impact on the exhaust gases. The best possible combination depends on the performance of what gases are to be eliminated, keeping the EGR rate at an optimum value between 10% and 20%. If preference is given to reduce NOx, then we will combine 10–20% EGR with SCR, but if the preference is given to reduce HC, CO, and soot, we will use 10% - 20% EGR in combination with a DPF. Overall, the DPF + SCR with 10% EGR rates seems to be an appreciable result.